(untitled) (African Journal of Biomedical Research, 2023)
Dental trauma is a public health problem, accounting for 17% of injuries to the body in those below the age of 6years compared to an average of 5% across all ages. It is more rampant among very young people. The prevalence in Nigeria is increasing. A prevalence of 10.8% was reported in Ibadan about a decade ago. The current study is therefore aimed at finding the prevalence of dental trauma in Ibadan. This was a cross-sectional study carried out among children aged 7 - 15 years in public schools in Ibadan North Local Government Area of Oyo State, Nigeria. Three primary and 3 secondary schools were selected. An interviewer-administered proforma was used to obtain information. Factors assessed were some predisposing factors of dental trauma, among which are Angle’s Class II division 1 malocclusion, increased over-jet, anterior open bite and lip competence. Data was analyzed using SPSS version 21 and the level of significance was set at p<0.05. Two hundred and thirty-five children participated in the study. There were 114(48.5%) males and 121(51.5%) females. Prevalence of dental trauma was 11.1%. None of the assessed factors that were statistically significant. The commonest dental trauma was Enamel fracture (Ellis class I), while the most affected teeth were the two upper central incisors. Also, more females and 10 – 12 years old had Enamel-Dentin-Pulp trauma. Dental trauma experience among the children in Ibadan in the last decade has not significantly changed. Teeth most commonly affected by dental trauma are the upper central incisors. The commonest dental trauma was Ellis class I.